2019
DOI: 10.1016/j.anai.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of weather and climate on pollen concentrations in Denver, Colorado, 2010-2018

Abstract: A B S T R A C TBackground: Increasing evidence indicates that climate change is affecting the timing of pollen season and concentrations of allergenic pollens. To date, pollen trends and their associations with meteorological variables have not been studied in most of the United States. Objective: The purpose of this study was to investigate the effects of weather and climate on pollen concentrations and pollen season timing in Denver, Colorado. Methods: We retrospectively analyzed tree, grass, and weed pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Similar trends in the course of lime pollen seasons were reported in a 10-year study conducted in Denver (Colorado, USA) [17]. The investigations also showed an accelerated onset of the pollen season of this taxon and an increase in the pollen concentration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar trends in the course of lime pollen seasons were reported in a 10-year study conducted in Denver (Colorado, USA) [17]. The investigations also showed an accelerated onset of the pollen season of this taxon and an increase in the pollen concentration.…”
Section: Discussionsupporting
confidence: 84%
“…In recent decades, many tree species, e.g. Betula [13,14], Acer [15], and Tilia [9,16,17], have been found response to global warming.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Grewling et al [ 54 ] reveals that daily concentrations of Betula pollen significantly increased on days with high mean temperatures. In many countries in Europe and the USA, a trend has been observed towards an earlier start of the pollen season in connection with climate change [ 4 , 18 , 21 , 55 , 56 ]. Moreover, Buters et al [ 57 ] found that temperature has a direct effect on Betula allergen release.…”
Section: Discussionmentioning
confidence: 99%
“…The major sensitizing pollen allergen involved in PFS in Northern Europe is birch tree pollen ( Betula verrucosa ); 66% of birch‐allergic UK adults and 48% of children have PFS, with the overall UK prevalence of PFS in an unselected adult population being 2% (range 1–4% depending on geography) 1,2 . The lengthening of the pollen season, prevalence of more allergenic pollen due to rising temperatures and increased severity of SAR all contribute to the growing prevalence of PFS in all ages 13–16 . In addition to SAR, other co‐morbidities associated with PFS are asthma, eczema (commonly in children) and gastro‐intestinal conditions such as irritable bowel syndrome (IBS) and eosinophilic oesophagitis (EoE) 17–20 …”
Section: Background and Epidemiologymentioning
confidence: 99%